ANALISIS PENGARUH KEPEMIMPINAN ISLAMI DAN ETOS KERJA ISLAMI TERHADAP KINERJA ISLAMI PEGAWAI DENGAN BUDAYA ORGANISASI ISLAMI SEBAGAI MODERATING VARIABEL (STUDI PADA RUMAH SAKIT ISLAM SITI HAJAR MATARAM) - M Aswadi; Lalu Suparman; Zainal Abidin (Master of Management, Mataram University, 2017)
This research is aimed at analyzing and determining the significance of the effect of Islamic leadership on the Islamic performance, analyzing and determining the significance of the effect of Islamic work ethic on the Islamic performance, analyzing and determining the significance of the effect of Islamic organizational culture on the Islamic performance, analyzing determining the significance of the leadership on the Islamic performance with Islamic organizational culture as moderating variable, and analyzing and determining the significance of the effect Islamic work ethic on the Islamic performance with Islamic organizational culture as moderating variable.The population of this research are all 261 employees working in Islamic Hospital of Siti Hajar Mataram. The sample were 72 respondent. The analysis were performance to examine the hypothesis with PLS-SEM analysis using smartPLS 3.0.The research showed that the Islamic leadership had positive but no significant effect on Islamic performance, the Islamic work ethic had positive and significant effect on Islamic performance, the Islamic organizational culture had positive and significant effect on the Islamic performance, the Islamic organizational culture did not strengthen the effect Islamic leadership on the Islamic performance, while the Islamic organizational culture strengthened the effect Islamic work ethic on the Islamic performance. Keywords : Islamic leadership, Islamic work ethic, Islamic organizational culture, Islamic performance.